2014
DOI: 10.1140/epjp/i2014-14266-0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental heat-bath cooling of spins

Abstract: Abstract. Algorithmic cooling (AC) is a method to purify quantum systems, such as ensembles of nuclear spins, or cold atoms in an optical lattice. When applied to spins, AC produces ensembles of highly polarized spins, which enhance the signal strength in nuclear magnetic resonance (NMR). According to this cooling approach, spin-half nuclei in a constant magnetic field are considered as bits, or more precisely quantum bits, in a known probability distribution. Algorithmic steps on these bits are then translate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 58 publications
0
34
0
Order By: Relevance
“…Based on this work, many cooling algorithms have been designed [6][7][8][9][10][11]. HBAC is not only of theoretical interest, experiments have already demonstrated an improvement in polarization using this protocol with a few qubits [12][13][14][15][16][17][18], where a few rounds of HBAC were reached; and some studies have even included the impact of noise [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this work, many cooling algorithms have been designed [6][7][8][9][10][11]. HBAC is not only of theoretical interest, experiments have already demonstrated an improvement in polarization using this protocol with a few qubits [12][13][14][15][16][17][18], where a few rounds of HBAC were reached; and some studies have even included the impact of noise [19].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this work, many cooling algorithms have been designed [6][7][8][9][10][11]. HBAC is not only of theoretical interest, experiments have already demonstrated an improvement in polarization using this protocol with a few qubits [12][13][14][15][16][17][18], where a few rounds of HBAC were reached; and some studies have even included the impact of noise [19].Through numerical simulations, Moussa [7] and Schulman et al [8] observed that if the polarization of the bath ( b ) is much smaller than 2 −n , where n is the number of qubits used, the asymptotic polarization reached will be ∼ 2 n−2 b ; but when b is greater than 2 −n , a polarization of order one can be reached. Inspired also by the work of Patange [20], who investigated the use of algorithmic cooling on spins bigger than 1 2 (using NV center where the defect has an effective spin 1), we investigate the case of cooling a qubit using a general spin l, and extra qubits which get contact with a bath.…”
mentioning
confidence: 99%
“…The current optimal control methods (GRAPE), and better ones such as a second order GRAPE [42] and Krotov based optimization [43] could enable various applications of AC in magnetic resonance spectroscopy [13,14,44] and maybe also other potential applications [45][46][47][48][49][50][51][52][53][54]. ln (4) (see [23]), where ε C,eq is the carbons' equilibrium polarization. On the right, the measured polarization and IC of C1 in each round.…”
Section: Discussionmentioning
confidence: 99%
“…on polarization enhancement) can be derived by interpreting the spin state in terms of information theory [22]. The information content (IC) of the spin was defined using the conventional notion of Shannon entropy H. The relation between a single spin's polarization and IC is given by the following equation [23,24] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation